2021
DOI: 10.1136/annrheumdis-2021-220761
|View full text |Cite
|
Sign up to set email alerts
|

Does biologic therapy impact the development of PsA among patients with psoriasis?

Abstract: ObjectiveTo examine the association of biologic therapy use for psoriasis with incident psoriatic arthritis (PsA) diagnosis.MethodsA retrospective cohort study was conducted in the OptumInsights Electronic Health Record Database between 2006 and 2017 among patients with psoriasis between the ages of 16 and 90 initiating a therapy for psoriasis (oral, biologic or phototherapy). The incidence of PsA was calculated within each therapy group. Multivariable Cox models were used to calculate the HR for biologic vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The authors demonstrated that biologic use was associated with the development of PsA among patients with psoriasis although acknowledged this may have been related to confounding by indication and protopathic bias. 63 It is therefore clear that further studies, in particular those that are prospective in nature, are required to further elucidate the relationship between risk and PsA development.…”
Section: Moving Towards Disease Preventionmentioning
confidence: 99%
“…The authors demonstrated that biologic use was associated with the development of PsA among patients with psoriasis although acknowledged this may have been related to confounding by indication and protopathic bias. 63 It is therefore clear that further studies, in particular those that are prospective in nature, are required to further elucidate the relationship between risk and PsA development.…”
Section: Moving Towards Disease Preventionmentioning
confidence: 99%
“… 58 This may be related to confounding by indication and protopathic bias, ie, when a pharmaceutical agent is inadvertently prescribed for an early manifestation of a disease that has not yet been diagnostically detected. 58 Indeed, studying the influence of systemic treatment in the transition from psoriasis to PsA is undermined by several issues. Patients need to be followed up longitudinally for a long period because arthritis develops on average of several years after initial diagnosis of psoriasis.…”
Section: Prevention Of Psa In Patients With Psoriasismentioning
confidence: 99%
“…Confounding by indication (ie, the reason for receiving a treatment, such as severe psoriasis, is also associated with the outcome of interest, such as PsA) and protopathic bias (ie, when a pharmaceutical agent is inadvertently prescribed for an early manifestation of a disease that has not yet been diagnostically detected) may distort the association between therapy and the development of the arthritis. 58 Assessing whether treating the skin disease with biologics may prevent development of arthritis, or instead treat early or mild forms of PsA that it is less clinically apparent is problematic. Predictive algorithms that use machine learning and related approaches may contribute to analyze relevant factors that settle disease from background events in the future.…”
Section: Prevention Of Psa In Patients With Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022 ARD will continue its path, striving to present breakthrough research activities across basic/translational and clinical/ outcomes sciences, already exemplified in this January issue, in which we learn about several studies on the potential prevention of the evolution of psoriatic arthritis in patients with psoriasis undergoing effective treatment, [28][29][30] accompanied by an editorial that summarises these findings and puts them into perspective. 31 But this edition harbours yet another publication, which for the first time appears simultaneously in all five EULAR and ACR journals, accompanied by a commentary from all five editors, making authors aware that all these journals will require adherence to ACR, EULAR and joint recommendations and criteria more strongly in future papers than done before.…”
Section: Incoming 2022: a Eular Anniversarymentioning
confidence: 99%